Reduced white matter integrity and cognitive deficits in maintenance hemodialysis ESRD patients: a diffusion-tensor study. - Zhang, Ruijie; Liu, Kai; Yang, Linfeng; Zhou, Tao; Qian, Shaowen; Li, Bo; Peng, Zhaohui; Li, Min; Sang, Shengpeng; Jiang, Qingjun; Sun, Gang (European Radiology, 2015)
Objectives: The purpose of this investigation was to examine the association between cognition disorders and microstructural white matter (WM) changes in maintenance hemodialysis end-stage renal disease (ESRD) patients.Methods: Twenty-six maintenance hemodialysis ESRD patients and 28 healthy controls underwent diffusion tensor imaging (DTI), Mini Mental State Examination (MMSE), Trial Marking Test-A&B (TMT-A&B), and white matter hyperintensity (WMH) assessment. Tract-based spatial statistics (TBSS) analyses was performed to evaluate WM changes in the patients. Relationships between behavioural performances, clinical data, and the DTI index were tested, respectively, by correlation analysis at the voxel level.Results: ESRD patients showed significant decreased fractional anisotropy (FA) in 14 WM regions, and increased mean diffusivity (MD) and radial diffusivity (RD) in widespread regions. Significant positive correlations between FA values and MMSE scores were found in the right anterior corona radiata and the left anterior thalamic radiation; significant negative correlations between the TMT-B time consumption and FA values were identified in the bilateral superior longitudinal fasciculus. Positive linear relationships between MD, RD values, and the duration of hemodialysis were found in several WM regions.Conclusion: Structural damages to radiation and associative fibre tracts, caused by brain oedema and WM demyelination, may account for the cognitive deficits in ESRD patients.